دور الرقابة في تحسين أداء المصارف الإسلامية في سورية دراسة ميدانية - حسون عتاب يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تواجه المصارف الإسلامية العديد من التحدِّيات المعاصرة التي أفرزتها الأحداث الدولية، والتحولات العالمية، ومحاولة التضييق على نمو واتساع المصارف الإسلامية وامتداد مظلتها على العالم كله، وكذلك الأخطاء والتجاوزات الشرعية والمصرفية التي وقعت فيها بعض المصارف الإسلامية. هذا الوضع يحتِّم على جميع المعنيين العمل على مواجهته، وفي مقدِّمتهم أعضاء هيئة الرقابة الشرعية لدى تلك المصارف، كما أنَّ الرقابة التي تمارسها المصارف المركزية على المصارف التقليدية والإسلامية تحظى بأهمية قصوى، ومع أنَّ هذه الرقابة قد زادت من كفاءة المصارف الإسلامية، إلا أنَّها لم تراعِ ظروف عمل هذه المصارف الخاضعة لأحكام الشريعة الإسلامية. من هنا جاء هذا البحث للتعرُّف على كيفية ممارسة الرقابة على المصارف الإسلامية في سورية. حيث تطرَّقت الباحثة إلى أنواع الرقابة على المصارف الإسلامية في سورية والمتمثِّلة بالرقابة الداخلية، رقابة المصرف المركزي والرقابة الشرعية. وتوصَّلت الباحثة في نهاية هذا البحث إلى مجموعة من الاستنتاجات من أهمّها: توجد فروق ذات دلالة معنوية بين أساليب الرقابة المصرفية المطبَّقة على المصارف التقليدية والإسلامية، كذلك وجود الرقابة الشرعية على أعمال المصارف الإسلامية أمر ضروري لضمان التزام هذه المصارف بأحكام الشريعة الإسلامية. في نهاية البحث تقدَّمت الباحثة بمجموعة من المقترحات والتوصيات وكان أهمها: ضرورة تطوير أساليب كميَّة ونوعيَّة للرقابة على أعمال المصارف الإسلامية لتحقيق أهداف الرقابة المرجوَّة في تحسين أداء المصارف الإسلامية، وكذلك ضرورة العمل على تخصيص إدارة مستقلة ضمن مصرف سورية المركزي، للقيام بأعمال التفتيش والرقابة على المصارف الإسلامية، مع تزويد هذه الإدارة بالعناصر البشرية المؤهلة والمدرَّبة على العمل المصرفي الإسلامي. Islamic banks face many contemporary challenges due to the international events, global transformations, and the attempt to restrict the growth and expansion of Islamic banks and its extension across the whole world, as well as errors and illegal and banking breaches that some Islamic banks has committed. This situation makes it imperative for all the stakeholders, first and foremost the Committee of Sharia in these banks, and the control exercised by central banks to Islamic and conventional banks is a paramount, and that such control has increased the efficiency of Islamic banks. It did not take into account the working conditions of these banks subject to the provisions of Islamic law (Sharia). Hence, this research is to learn how to exercise control over the Islamic banks in Syria. The researcher addressed the types of control on Islamic banks in Syria represented by the internal control and supervision of the Central Bank and the Shari’a. The researcher presented at the end of this research a set of conclusions: there are significant differences between the banking control methods imposed on Commercial and Islamic banks, as well as the existence of legal supervision of Islamic banks is necessary to ensure that the provisions of the Islamic law. Eventually, the researcher concludes a set of proposals and recommendations, including: the need to develop qualitative and quantitative methods to control the work of the Islamic banks to achieve desired control objectives in improving the performance of Islamic banks, as well as the need to allocate a separate department within the Central Bank of Syria, to carry out inspection and control of Islamic banks, while providing the Department with trained and qualified human resources on Islamic banking.